2021
DOI: 10.1155/2021/9537680
|View full text |Cite
|
Sign up to set email alerts
|

Snail Shells Adsorbent for Copper Removal from Aqueous Solutions and the Production of Valuable Compounds

Abstract: This research explored the efficiency of snail shells powder (SSP) for Cu(II) removal from aqueous solutions and the production of valuable compounds from the residual product. To confirm its chemical and mineral components, the material was characterized by different instrumental techniques. The effects of experimental parameters such as the pH of the solution, the effect of SSP dose, particle size, and initial concentration of Cu(II) on the removal process were studied. The removal of Cu(II) was reasonably f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 75 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…After sintering at 700 1C, the predominant phase of CaCO 3 was calcite, while CuO and CaO were the secondary phases. 278,280 Each XRD pattern changed from 29.441 to 26.241 when heated from 105 to 700 1C. SEM analysis revealed large, irregular particles of HAp, with the finest measuring 26.9 mm and the largest, 322 mm.…”
Section: And 284mentioning
confidence: 99%
“…After sintering at 700 1C, the predominant phase of CaCO 3 was calcite, while CuO and CaO were the secondary phases. 278,280 Each XRD pattern changed from 29.441 to 26.241 when heated from 105 to 700 1C. SEM analysis revealed large, irregular particles of HAp, with the finest measuring 26.9 mm and the largest, 322 mm.…”
Section: And 284mentioning
confidence: 99%
“…When the contact time increases, the adsorption efficiency increases as well, but after a certain threshold, the effect saturates and no longer increases. When investigating the influence range of 0 to 180 min, Redouane Ouaf et al found the highest Cu(II) removal efficiency at 90 min in a study on snail shells [ 109 ]. A study of Cd 2+ treatment at pH 6 over a survey period of 10 to 80 min found that treatment efficiency was lowest at 10 min and highest at 60 min.…”
Section: Effect Of Nutrient To Adsorption Biocharmentioning
confidence: 99%
“…In addition to the important influencing parameters listed above, some studies also evaluated the effect of different particle sizes and the ratio of admixture on adsorption efficiency or ionic strength on adsorption capacity. Specifically, in the study of Redouane Ouaf and colleagues, the different particle sizes were evaluated from 50 to 800 μm and the results showed that the effect of particle size on waste removal efficiency was not significant [ 109 ]. However, when comparing the effect, it is a good choice for the shell adsorbent for particle sizes larger than 300 μm.…”
Section: Effect Of Nutrient To Adsorption Biocharmentioning
confidence: 99%